Monk, official and gentry: multiple writings of jingshan annals and the regional sight of the late ming buddhist revival: multiple writings of jingshan annals and the regional sight of the late ming buddhist revival - Li, Yang (2022)
When discussing the revival of Buddhism in the late Ming Dynasty, scholars lack the study of rich local records, specific regions and typical cases. Jingshan temple in Hangzhou provides such a sample. An outstanding manifestation of Jingshan Temple in the late Ming Dynasty is the emergency of a whole bunch of annals. Different groups such as monks, magistrates, and gentry all participated in the writing of the history of Jingshan diachronically in the same space. Different versions of Jingshan Annals reveal the interweaving of historical events, trends of the times, and the wishes of various groups in distinct regions, shedding light on the development that Buddhist historical records began to involve other classics outside Buddhism instead of only focusing on Buddhist sutras. This process manifests that the revival of Buddhism in the late Ming Dynasty is also a diachronic active state achieved by the people’s activities with different purposes in a specific area.